2012
DOI: 10.3989/scimar.03101.18d
|View full text |Cite
|
Sign up to set email alerts
|

Marine benthic cartography of the Cap de Creus (NE Catalan Coast, Mediterranean Sea)

Abstract: SUMMARY:The marine benthic cartography of the Cap de Creus and surrounding areas (NW Mediterranean Sea) was obtained by combining classical grabbing methods with more recent imaging methods based on a remotely operated vehicle. The goals of this particular survey can be summarized as follows: 1) to chart the benthic communities (and the area of each one); 2) to evaluate the benthic diversity of the areas; 3) to produce visual documentation of the distributions of the benthic organisms; 4) to identify human-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The few aggregations of P. spinosum and V. cynomorium were found at about 50 m depth, although some specimens were recorded at unusual depths in the area if compared with data in the literature (Supplementary Material Table S1). We found that 70% of the occurrences of V. cynomorium in our study area were detected above 100 m and three colonies were even found at an unusual depth of 372 m, despite the fact that these two species are known to be continental-shelf species with a distribution related to terrigenous sediments (Gili and Pagès 1987, Williams 2011, Sardá et al 2012. López-González et al (2001) reported, in the eastern Atlantic, a wider depth range (25-188 m) than Williams (1990, 13-91 m), and Gili and Pagès (1987) showed an even deeper limit in the Mediterranean Sea (around 260 m).…”
Section: Aggregations Of Pennatula Spp On Circalittoral Soft Bottomsmentioning
confidence: 88%
“…The few aggregations of P. spinosum and V. cynomorium were found at about 50 m depth, although some specimens were recorded at unusual depths in the area if compared with data in the literature (Supplementary Material Table S1). We found that 70% of the occurrences of V. cynomorium in our study area were detected above 100 m and three colonies were even found at an unusual depth of 372 m, despite the fact that these two species are known to be continental-shelf species with a distribution related to terrigenous sediments (Gili and Pagès 1987, Williams 2011, Sardá et al 2012. López-González et al (2001) reported, in the eastern Atlantic, a wider depth range (25-188 m) than Williams (1990, 13-91 m), and Gili and Pagès (1987) showed an even deeper limit in the Mediterranean Sea (around 260 m).…”
Section: Aggregations Of Pennatula Spp On Circalittoral Soft Bottomsmentioning
confidence: 88%
“…Since 2003, the benthic habitats of the Cap de Creus (littoral zone, continental shelf and submarine canyon) have been studied (Orejas and Gili 2009, Gili et al 2011, Sardá et al 2012. Several European (INTER-REG, HERMES) and national (DEEPCORAL) projects have provided the basis for a better understanding of the ecology in the area.…”
Section: Study Areamentioning
confidence: 99%
“…During the evaluation phase of the Cap de Creus region to assess its potential interest for conservation, recorded images from remotely operated vehicles (ROVs) and manned submersibles were used. High abundance of cables and abandoned fishing gears was observed in the videos, demonstrating a high impact of these fishing activities on the littoral zone, continental shelf and slope (Gili et al 2011, Sardá et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cartography not only represents the spatial location of marine habitats and geomorphic features (Miccadei, Orru, Piacentini, Mascioli, & Puliga, 2012;Rovere et al, 2010;Sardá, Rossi, Martí, & Gili, 2012), but also allows, through the use of geographic information systems (GIS), the modeling of different management scenarios (Fraschetti et al, 2005;Montefalcone et al, 2013;Parravicini et al, 2012;Vassallo, Paoli, Rovere, & Montefalcone, 2013). Mapping of terrestrial information is largely reported in the literature (Finn, 2011;López-García & Guzmán, 2010;Rose & Smith, 2008;Sahlin & Glasser, 2008), and takes advantage of numerous survey techniques such as satellite imagery, aerial photos, LIDAR or high-accuracy GPS (Bowles & Cowgill, 2012;Palamara, Dickson, & Kennedy, 2007;Storrar, Stokes, & Evans, 2013).…”
Section: Introductionmentioning
confidence: 99%